International tourism : cultures and behavior - Reisinger, Yvette (Amsterdam, 2009)
In recent years there has been a considerable interest in the cultural aspects of tourism such as the impacts of culture on tourism planning, development, management, and marketing. However, the focus has been on material forms of culture such as arts, music, or crafts. The impacts of national culture on tourist behavior and travel decision-making have not been paid much attention. Only in the last two years have cross-cultural issues begun to generate significant interest among academics. An examination of cultural characteristics and differences is extremely important to the tourism industry because today's tourism environment is becoming increasingly international. Information on the nature of the cultural differences between international tourists and locals is not readily available in tourism literature. The concept of culture is very complex and includes such abstract concepts as satisfaction, attitude and loyalty. International Tourism brings these concepts to the undergraduate student in tourism, as well as students in the related fields of marketing, management, international business, and cross-cultural communication. Designed as a textbook, it isorganized and presented in an integrated and relevant way for the benefit of a worldwide audience
Keywords: Culture and tourism; Tourism